2015
DOI: 10.1186/s12885-015-1185-1
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of hot beverages and foods and the risk of esophageal cancer: a meta-analysis of observational studies

Abstract: BackgroundPrevious studies have mostly focused on the effects of specific constituents of beverages and foods on the risk of esophageal cancer (EC). An increasing number of studies are now emerging examining the health consequences of the high temperature of beverages and foods. We conducted a meta-analysis to summarize the evidence and clarify the association between hot beverages and foods consumption and EC risk.MethodsWe searched the PubMed, Embase, and Web of Science databases for relevant studies, publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 60 publications
3
48
0
1
Order By: Relevance
“…12 Among dietary factors, fruit and vegetable intake is protective, 13 while intake of red meat 14 and very hot beverages are risk factors. 15 Genetic factors are also involved; a pooled analysis of three genome-wide association studies found new susceptibility loci for OSCC. 16 Tobacco smoking cessation is probably the single most effective primary preventive measure.…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%
“…12 Among dietary factors, fruit and vegetable intake is protective, 13 while intake of red meat 14 and very hot beverages are risk factors. 15 Genetic factors are also involved; a pooled analysis of three genome-wide association studies found new susceptibility loci for OSCC. 16 Tobacco smoking cessation is probably the single most effective primary preventive measure.…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%
“…A mild increase in temperature (37–41°C) creates a significant disturbance to these junctions, leading to increased epithelial permeability . A deficient barrier caused by heat increases the risk of esophageal damage by subsequent contact with refluxed gastric acid, intraluminal carcinogens, bacterial translocation and other noxious substances. Heat also affects other types of intercellular junctions, including Gap junctions and transporter proteins .…”
Section: Heat Stressmentioning
confidence: 99%
“…Environmental factors are most often discussed in the origin of ESCC, including the consumption of very hot beverages and food, a low intake of fresh fruit and vegetables, alcohol consumption, cigarette smoking and low socioeconomic status. Recently, two meta‐analyses showed that the consumption of hot beverages and food were significantly associated with ESCC …”
Section: Introductionmentioning
confidence: 99%
“…However, De Jong and colleagues showed that drinking hot coffee (65°C) could increase intra-esophageal temperature by 6 – 12°C 27 , and an endoscopic survey in southern Brazil demonstrated that drinking very hot maté was associated with esophageal injury (esophagitis) 28 . Recent systematic reviews and meta-analyses have demonstrated an association between ingesting hot temperature food and beverages and ESCC 15,29,30 . A working group from the IARC has now classified very hot beverages as possibly carcinogenic 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of hot food and beverages has been proposed as a risk factor for esophageal cancer in a number of different geographical locations 15 , including drinking hot maté in South America 16 ; drinking hot tea in Iran 17,18 ; and consumption of hot food and beverages in China 19,20 . Recently, the International Agency for Research on Cancer (IARC) defined drinking temperatures above 65°C as “very hot” and considered this exposure as probably carcinogenic (Group 2A) 21,22 .…”
Section: Introductionmentioning
confidence: 99%